Al-Qur’an, Tafsir Ilmiah, dan Ilmu Pengetahuan - Jaenuri, Jaenuri (Research and Development Institution, Darussalam Institute for Islamic Studies, 2021)
Allah revealed the Qur’an as a guide for humankind throughout the ages. Therefore, the effort to understand the Qur’an is interpretation, an attempt to understand the direction and will of Allah and the operationalization of that will in human life, in all fields of faith, worship, and muamalah. Dialogue between Islamic civilization and civilizations of Greece, India, and Persia began with the translation of some of their works during the golden age of Islam. It has influenced the birth of various methods and schools of interpretation of the Qur’an. In addition, there are also different patterns of interpretation of the Qur’an. There are nuances of fiqhi, balaghi, isyari, even kalami or philosophy. It was also found that the ‘scientific interpretation’ method was oriented to the use of findings in the field of science to prove the various truths of scientific facts mentioned in the Qur’an. The discourse linking science and the Qur’an always developed. The pattern of scientific interpretation in the treasures of the science of interpretation of the Qur’an raises pros and cons among scholars and commentators. This article aims to explore the relationship between the Qur’an and science the efforts to understand the Qur’anic form of interpretation. The Qur’an is not only able to answer or respond to cultural problems related to social, political, economic, and religious conditions at the time the Qur’an was revealed. But it will also be a solution to all the issues of the times. Therefore, it is necessary to try to interpret and deepen the verse as a bridge to understand the Qur’an. The interpretation is the product of human thought and civilization so it is always developing and influenced by the dynamics of human civilization, so that in its journey,